2014
DOI: 10.1007/s12288-014-0339-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Interleukin 1β Serum Level in Different Responder Groups and Stages of Chronic Myeloid Leukemia Patients on Imatinb Mesylate Therapy

Abstract: Chronic myeloid leukemia (CML) is a myeloproliferative disorder characterized by the presence of an acquired mutation which affects the hematopoietic stem cell, leading to a striking overproduction of immature granulocytes. The first important clue to its pathogenesis the Philadelphia chromosome created by a reciprocal translocation between chromosomes 9 and 22 (t [9; 22] [q34; q11]). The development of the BCR-ABL-targeted imatinib mesylate represents a paradigm shift in the treatment of CML. Imatinib display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…There are reports of a high concentration of various inflammatory cytokines in ALL associated with the presence of infection or in response to chemotherapy (25)(26)(27)(28). However, there are no reports of an initial inflammatory process in newly diagnosed patients with ALL without apparent infection.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of a high concentration of various inflammatory cytokines in ALL associated with the presence of infection or in response to chemotherapy (25)(26)(27)(28). However, there are no reports of an initial inflammatory process in newly diagnosed patients with ALL without apparent infection.…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated the enhanced level of TNF-α in chronic leukemia and acute lymphoblastic leukemia (ALL), but not in AML (Aguayo et al, 2000). IL-6 concentration is also found higher in CLL patients than healthy individuals (Reittie et al, 1996) and the high level of IL-1β is associated with poor prognosis in CML (Matti et al, 2014). The enhanced serum levels of the cytokines IL-6, TNF-α and IL-1β was exhibited in myeloid compartment of mice lacking A20 (Matmati et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown that IL-6 concentration is higher in leukemia patients including CLL and AML (Reittie et al, 1996;Zhang et al, 2020). IL-1β is a potent pro-inflammatory cytokine for host defense responses to infection and injury, and high level of IL-1β is associated with poor prognosis in CML (Matti et al, 2014).…”
Section: Introductionmentioning
confidence: 99%